2014
DOI: 10.1080/17470218.2013.863373
|View full text |Cite
|
Sign up to set email alerts
|

A Configural Dominant Account of Contextual Cueing: Configural Cues are Stronger than Colour Cues

Abstract: Previous work has shown that reaction times to find a target in displays that have been repeated are faster compared with displays that have never been seen before. This learning effect, termed 'contextual cueing' (CC), has been shown using contexts such as the configuration of the distracters in the display and the background colour. However, it is not clear how these two contexts interact to facilitate search. We investigated this here by comparing the strengths of these two cues when they appeared together.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 59 publications
(134 reference statements)
1
21
0
Order By: Relevance
“…Furthermore, it was recently reported that repeated configurations provide a stronger cue than repeated color information (Kunar, Johnston, & Sweetman, 2014), substantiating the notion that spatial information is a central factor in CC. Accordingly, prominent models of CC have often emphasized the spatial domain in context learning (e.g., Brady & Chun, 2007;Jiang & Wagner, 2004;Olson & Chun, 2002).…”
mentioning
confidence: 55%
“…Furthermore, it was recently reported that repeated configurations provide a stronger cue than repeated color information (Kunar, Johnston, & Sweetman, 2014), substantiating the notion that spatial information is a central factor in CC. Accordingly, prominent models of CC have often emphasized the spatial domain in context learning (e.g., Brady & Chun, 2007;Jiang & Wagner, 2004;Olson & Chun, 2002).…”
mentioning
confidence: 55%
“…Both conditions consisted of a Training Phase, which established learning, and a Test Phase, which measured CC (see also Brady & Chun, 2007, Makovski & Jiang, 2010, Kunar & Wolfe, 2011, Kunar, John & Sweetman, 2014. The Training Phase consisted of seven epochs (Epochs 1-7).…”
Section: Design and Proceduresmentioning
confidence: 99%
“…In addition to learning distractor-distractor relationships, there is evidence that nonconfigural Bbackground^cues, such as colors, textures, or natural scenes, can support contextual cuing (e.g., Brockmole, Castelhano, & Henderson, 2006;Kunar, Flusberg, & Wolfe, 2006). The role of these background cues depends on their salience and can overshadow cuing driven by the configuration of the array items themselves (Rosenbaum & Jiang, 2013), though this may depend on the specific background cues that are present (Kunar, John, & Sweetman, 2014). Taken together, the existing research suggests that learning of target-distractor associations, distractor configurations, as well as other nonconfigural background information, all contribute to contextual cuing.…”
Section: Role Of Associative Learningmentioning
confidence: 99%